IN VITRO ANTIBACTERIAL ACTIVITIES OF OPUNTIA FICUS INDICA STEM AND FRUIT EXTRACTS USING DISC DIFFUSION METHOD - Gnanakalai, Kannusamy; Gopal, Rengaswamy (International Journal of Current Pharmaceutical Research, 2016)
Objective: Opuntia ficus indica is a medicinal plant belonging to family Cactaceae. It is a species of cactus that has long been a domesticated crop plant important in agricultural economies throughout arid and semiarid parts of the world. The fruit and stem are used to prepare worth added products, fruits jam, squash, drinks, preserve product of pickle, body lotion, shampoo and creams, etc. Methods: For the preliminary study, various extracts of stem and fruit has been used to check the efficacy of antibacterial activity against Bacillus subtilis, Pseudomonas aeruginosa and Escherichia coli bacteria of gram-positive and gram-negative strain respectively using disc diffusion method. Results: The stem and fruit extracts showed various levels of activity on different test organisms. The methanol fruit extracts showed high antibacterial activity against Escherichia Coli, Pseudomonas aeruginosa and Bacillus subtilis compared with other extracts. Aqueous extract of stem and fruit showed less antibacterial activity against the tested bacterial strains. Conclusion: The present study suggests that the methanol extracts of the fruit of Opuntia ficus indica contain compounds that can form the basis for the development of a novel broad-spectrum antibacterial formulation.